Advanced Hepatocellular Carcinoma. Issue 5 (September 2015) - Lee, Sang Ho; Hayano, Koichi; Zhu, Andrew X.; Sahani, Dushyant V.; Yoshida, Hiroyuki
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to find prognostic biomarkers in perfusion computed tomography (PCT)–based kinetic parameters for advanced hepatocellular carcinoma (HCC) treated with antiangiogenic chemotherapy. Methods Twenty-two patients with advanced HCC underwent PCT imaging and subsequently received bevacizumab in combination with gemcitabine and oxaliplatin. Pretreatment PCT data within advanced HCC were analyzed using the Tofts-Kety, 2-compartment exchange, adiabatic approximation to the tissue homogeneity (AATH), and distributed parameter models. Blood flow, blood volume, extraction fraction (E), and other 3 parameters were calculated. Kinetic parameters in each model were evaluated with 1-year survival discrimination using Kaplan-Meier analysis and with overall survival using univariate Cox regression analysis. Results Only the AATH model–derived E was statistically significantly prognostic for 1-year survival. The increased AATH model–derived E was significantly associated with longer overall survival (P = 0.005). Conclusions The AATH model–derived E was an effective prognostic biomarker for advanced HCC.